2016
DOI: 10.3310/hta20950
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness and cost-effectiveness of surgical options for the management of anterior and/or posterior vaginal wall prolapse: two randomised controlled trials within a comprehensive cohort study – results from the PROSPECT Study

Abstract: BackgroundThe use of mesh in prolapse surgery is controversial, leading to a number of enquiries into its safety and efficacy.ObjectiveTo compare synthetic non-absorbable mesh inlay, biological graft and mesh kit with a standard repair in terms of clinical effectiveness, adverse effects, quality of life (QoL), costs and cost-effectiveness.DesignTwo randomised controlled trials within a comprehensive cohort (CC) study. Allocation was by a remote web-based randomisation system in a 1 :1 : 1 ratio (Primary trial)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 75 publications
1
22
0
1
Order By: Relevance
“…Our findings are consistent with a previous UK analysis, which also found mesh augmentation to be cost‐ineffective . The findings of a second economic evaluation were inconclusive; however, the results are not directly comparable because they included women with AC and/or posterior colporrhaphy …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings are consistent with a previous UK analysis, which also found mesh augmentation to be cost‐ineffective . The findings of a second economic evaluation were inconclusive; however, the results are not directly comparable because they included women with AC and/or posterior colporrhaphy …”
Section: Discussionsupporting
confidence: 89%
“…The risk of surgically managed recurrence following a secondary repair was based on an observational cohort study . This study did not report the anatomical recurrence rate so this was taken from a UK‐based RCT . The annual probabilities were estimated as described above for the primary repair.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also examples of studies which have used expert opinion [13,14] or analyst assumptions [15,16]. For many cost-effectiveness models there is insufficient information reported to reliably gauge the methods used to extrapolate healthcare costs and utilities for health states and clinical events, including for example Glazener et al [17], where it is not clear how costs observed at 2 years within the PROSPECT study were extrapolated over the 5 and 10 year time horizons.. In such instances the focus seems to be on describing extrapolation methods used for the effectiveness evidence while glossing over the assumptions and methods used to extrapolate costs and utilities, let alone assessing the implications of these assumptions in term of any decision uncertainty.…”
Section: Assessing the Methodologies Used To Extrapolate Costs And Utmentioning
confidence: 99%